Transformative Learning Strategies in an Effort to Improve Critical Thinking Skills - Saihul Atho Alahul Huda; Amirul Mirza Ghulam Sri Utami (SCHOOLAR: Social and Literature Study in Education, 2025)
This research aims to examine Transformative Learning Strategies in Efforts to Improve Critical Thinking of Basic Cadre Training Participants of PMII Tabassam Rayon, Wahab Hasbullah Jombang Commissariat. The approach used in this research is qualitative, with data collection methods through in-depth interviews with organizational administrators of PMII Tabassam Rayon, Wahab Hasbullah Jombang Commissariat.The results of the interview show that transformative learning strategies can influence the critical thinking of participants in PMII basic cadre training. This is proven by what the Head of Rayon said that transformative learning strategies enable participants to stimulate their thinking power for knowledge, and the development of knowledge also influences courage. participants in conveying ideas and notions, as well as making them aware of the shackles of naivety and social reality. Thus, transformative learning has proven to be effective as learning that can improve the critical thinking of participants who take part in PMII Rayon Tabassam basic cadre training. This research suggests that the PMII organization can perfect learning strategies in education which of course takes an adult and liberating approach.